Implementation of Character Learning Through the Content of the Quran and Local Wisdom Based on Technology - Eka Nurul Amalia; Ridha, Arif; Arifin, Zainul; Zainal, Zainal (Ahlussunnah: Journal of Islamic Education, 2023)
Technological developments have had a tremendous impact on all areas of life, one of which is education. On the one hand, the world of education has developed rapidly with the emergence of various technology-based learning media that help in achieving the nation's ideals in the world of education. Learning resources also seem very easy to obtain by making use of various platforms on the Internet. However, on the other hand, technology actually has a negative impact on the world of education. The abundance of information obtained by students in this category who are teenagers, leads them to moral damage due to not being able to filter all incoming information. Western culture which is not in accordance with the nation's personality is also easy to influence them. In this case, character education must always be intensified for students for the good of the nation. Therefore, the author took the initiative to create learning innovations-books Mathrest which integrates local wisdom and Quranic verses in shaping the character of the nation's generation. In preparing this paper, the author used the Research and Development (R&D) method. In the process of searching for data and needs, the author uses literature review data collection techniques as the main focus. The research results found that Mathrest was able to provide students with the provisions to live life as they should. Mathrest is also designed using various illustrations and made like a comic with the aim of making learning not only meaningful but also prioritizing the fun aspect for students.